THE ANALYSIS, IDENTIFICATION, AND FORMULATION OF METALLOTHIONEIN EXTRACT AVAILABLE IN ROOTS, STEMS, LEAVES , FLOWERS , AND GRAINS OF RICE, CORNS, BEANS , AND SOYBEANS - Budi Santosa; Henna Rya Sunoko; Andri S (International Journal of Science and Engineering, 2016)
Abstract –Vegetable materials are easily found around us but are frequently considered useless. The Metallothionein content in vegetable materials such in roots, stems, leaves, flowers, and fruit of rice, corns, beans, and soybeans has not been investigated before.  Metallothionein protein has the role to bind heavy metals and serves as means of detoxification of heavy metals. This studi investigated to analyze, identify, and formulate metallothionein extracts from vegetable materials such as in roots, stems, leaves, flowers, and fruit of rice, corns, beans, and soybeans. The Experimental, each vegetable material available in roots, stems, leaves, flowers and fruit of rice, corns, beans, and soybeans was made into simplisia (crude medication) ​​and then was processed into infuse. ELISA method was conducted as the measurement techniques upon protein level of each vegetable material infuse. The levels of Metallothionein protein available in vegetable materials were identified to determine the highest. The extract formula was taken from the highest levels of metallothionein. The result showed that the average metallothionein protein level from the entire vegetable materials was 0.62 ng: the highest in rice leaves of 1.4 ng and the lowest in bean flowers of 0.2 ng. The rice leaves were further formulated into metallothionein Extract. The analysis of metallothionein levels of vegetable materials such as in roots, stems, leaves, flowers, and fruit of rice, corns, beans and soybeans found that the highest level was in rice leaves of 1.354539 ng, and the lowest was in bean flowers of 0.22478.   Key Words - Vegetable, metallothionein..